Development of Competency Standards for Automotive Technology Program - CEZAR B. BELEBER (Mathematical Statistician and Engineering Applications, 2022)
This study was conducted to find out the degree of significance of competencies in knowledge domain, skills and work attitude in automotive technology and developed competency standards for Automotive Technology program. Conducted from January 6 to February 25, 2020, the data were gathered from 60 respondents composed of 20 recognized automotive technicians from industry or the well-known automotive companies; 20 famous automotive entrepreneurs who run a small automotive service shops, skilled and well-known for their expertise on this specific field; and 20 automotive instructors/professors from the academe and training centers in Iloilo City and province. The PMDEE process in competency standards development was utilized that includes Profiling, Mapping, Designing and Development, Expert Validation and Evaluation. The results revealed that the entire competencies in knowledge domain, skills and work attitude of the proposed competency standards for Automotive Technology program were rated as “very significant” as evaluated by the recognized automotive technicians from industry, automotive entrepreneurs and automotive instructors/professors from the academe since the respondents found all the items of the developed competency standards to be “very significant”, it implies that each competency in knowledge domain, skills and work attitude of the proposed competency standards were very important and must be included in the competency standards for Automotive Technology program. Furthermore, findings led to the conclusion that perceptions in knowledge domain, skills and work attitude of automotive technicians from the industry, automotive entrepreneurs and automotive instructors/professors from the academe were almost the same as to the degree of significance of the underpinning competencies. As an offshoot of the study, a competency standards for Automotive Technology program was crafted and developed and was “very acceptable” in terms of physical aspects, contents, learning competencies and evaluative measures. The developed competency standards for Automotive Technology program may be used in order to ensure the congruency and to avoid the “mismatch” and skills gap of competencies being taught in the academe to what are practiced in the automotive industry.